Pengaruh Belanja Daerah Investasi dan Kurs Terhadap Pertumbuhan Ekonomi DKI Jakarta Periode 1987 – 2017 - Yurianto Yurianto (Universitas Indraprasta PGRI, 2020)
Jakarta's economic growth plays an important role in the national economy. For this reason, it is necessary to identify the factors that influence the Jakarta’s economic growth. The purpose of this study is to describe the development of economic growth, investment, the exchange rate of the rupiah against the US dollar and the allocation of regional spending and analyze the effect of regional spending, investment, exchange rates, economic crisis on the Jakarta’s economic growth period 1987-2017. The analysis method is quantitative and descriptive qualitative methods. The results of the analysis, the coefficient of determination (R2) reaches 0.912. The ratio of goods, services and capital expenditure to total expenditure and investment has a positive and significant effect on economic growth while the depreciation of the rupiah against the United States dollar and the economic crisis have a negative impact.